Director’s Duty to Employees: Co-Relation Between Corporate and Labour Laws - Hesty Diyah Lestari (Fakultas Hukum Universitas Gadjah Mada, 2011)
Labour law does not always provide a satisfactory answer to the issue on the protection of workers’ or employees’ interests. Modern corporate law gives an alternative way in promoting the interests of employees; whereby it obliges directors to take into account not only shareholders’ but also employees’ interests in decisionmaking process. Hukum perburuhan tidak selalu memuaskan dalam melindungi kepentingan buruh atau pegawai perusahaan. Hukum perusahaan yang modern memberikan alternatif untuk memajukan kepentingan para pegawai perusahaan, di mana ia menentukan agar direktur dalam mengemban tugasnya pada perusahaan, tidak hanya memperhatikan kepentingan pemegang saham tetapi juga harus memperhatikan kepentingan pegawai dalam proses pengambilan keputusan.